Incidence, Outcomes, and Prediction of Postoperative Urinary Retention After a Nonurologic Procedure. (May 2020) - Abdul-Muhsin, Haidar M.; Jakob, Nicholas; Cha, Stephen; Zhang, Nan; Schwartz, Adam; Navaratnam, Anojan; Khan, Aqsa; Humphreys, Mitchell
Abstract : Purpose: To develop a prognostic model to estimate postoperative urinary retention (POUR) after lower limb arthroplasty. Methods: One thousand two hundred twenty patients underwent 1, 374 joint replacement operations (812 knees and 562 hips) between December 2008 and May 2014. Detailed variables were collected. A multivariable logistic regression model was used to identify the independent predictors for POUR. Boot strapping and stepwise elimination was used to design a predictive nomogram. Results: There were 124 incidents of POUR (9.02%) in 118 patients (90 knee, 34 hip, P = 0.001). On univariate analysis, patients who developed POUR were older ( P < 0.001), had higher American Association of Anesthesiology scores (P = 0.007), underwent knee replacement (0.001), were obese (body mass index > 35) ( P = 0.04), and were hypertensive ( P = 0.029), with a history of benign prostatic hyperplasis (BPH) ( P < 0.001) or neurologic disorders ( P = 0.024). On multivariable analysis, age (60 to 69 years, P = 0.023, 70 to 79 yrs P = 0.008, >80 years P = 0.003), knee replacement ( P = 0.014), and history of BPH ( P = 0.013) were the independent predictors of POUR. A score was assigned to each predictor (total = 31). The C-index was 0.65. There were three risk categories as follows: 0 to 50, 51 to 85, and 86+ points resulting in 3.3%, 7.2%, and 14.0% risk of retention, respectively. Discussion: This nomogram reliably predicts the risk of POUR in patients undergoing hip and knee arthroplasties and may help planning preoperative interventions to decrease the risk of this complication.